Origins of Mapungubwe Project: test excavations at Den Staat 14B and 14C - Huffman, T. N. (Southern African Humanities, 2017)
Two Leopard’s Kopje homesteads in the Limpopo Valley yielded the burnt remains of decorated grainbins, echoing the ‘breast and furrow’ pattern found on nineteenth century Shona material culture. The burnt granaries were the result of cleansing rituals associated with severe droughts in the twelfth and thirteenth centuries. Nearby storage pits yielded TK2 pottery, exemplifying typical assemblages from commoner homesteads. Pits in the female grainbin and male kraal zones originally served different purposes, and expand the recorded features representing the Central Cattle Pattern.